Aflatoxins, fumonisins, and trichothecenes: a convergence of knowledge. Issue 1 (20th November 2012) - Woloshuk, Charles P.; Shim, Won‐Bo
Abstract Plant pathogenic fungi Aspergillus flavus, Fusarium verticillioides, and Fusarium graminearum infect seeds of the most important food and feed crops, including maize, wheat, and barley. More importantly, these fungi produce aflatoxins, fumonisins, and trichothecenes, respectively, which threaten health and food security worldwide. In this review, we examine the molecular mechanisms and environmental factors that regulate mycotoxin biosynthesis in each fungus, and discuss the similarities and differences in the collective body of knowledge. Whole‐genome sequences are available for these fungi, providing reference databases for genomic, transcriptomic, and proteomic analyses. It is well recognized that genes responsible for mycotoxin biosynthesis are organized in clusters. However, recent research has documented the intricate transcriptional and epigenetic regulation that affects these gene clusters. Significantly, molecular networks that respond to environmental factors, namely nitrogen, carbon, and pH, are connected to components regulating mycotoxin production. Furthermore, the developmental status of seeds and specific tissue types exert conditional influences during fungal colonization. A comparison of the three distinct mycotoxin groups provides insight into new areas for research collaborations that will lead to innovative strategies to control mycotoxin contamination of grain.